Effects of Ti–Al Complex Deoxidization Inclusions on Nucleation of Intragranular Acicular Ferrite in C–Mn Steel. Issue 4 (24th June 2015) - Huang, Qi; Wang, Xinhua; Jiang, Min; Hu, Zhiyong; Yang, Chengwei
Abstract : The influences of Ti–Al complex deoxidation inclusions on nucleation of intragranular acicular ferrite (IAF) in C–Mn steel have been investigated based on four specimens with different Ti and Al contents. The inclusions of Steel 1 and Steel 2 both containing high Al are detected as Al2 O3 and Ti3 O5  · Al2 O3, respectively. Owing to the low concentration of Mn in these inclusions, the manganese depletion zones (MDZs) which act as predominant driving force of IAF nucleation could not form easily. In Steel 3, Ti3 O5 –MnS is found as the main inclusion, which could be considered as potent nucleus. However, the excessive Ti leads to the aggregation of numerous inclusions less than 1 µm at grain boundaries, consequently restraining the nucleation of IAF. The main inclusions of Steel 4 containing low Al and medium Ti are found as Ti3 O5  · Al2 O3  · MnO, which effectively facilitate IAF nucleation. The size of inclusions mainly distributes in optimum zone corresponding to the maximum possibility of IAF nucleation. Therefore, the Al should be controlled as low as possible to ensure the nucleating effectivity of inclusion. While Ti should be appropriately controlled at medium level to distribute the inclusion size in the optimum zone to obtain well‐developed microstructures of IAF in C–Mn steel. Abstract : The current work investigates the influences of Al and Ti contents on IAF formation. The results show that the Al should be controlled as low as possible for the effectiveness of inclusion nucleating IAF. While Ti should be appropriately controlled at medium level in order to distribute the inclusion size in optimum zone to obtain well‐developed microstructures of IAF.